Positive Imagery Training Increases Positive Self-Referent Cognition in Depression - Dainer-Best, Justin (Behav Res Ther, 2018)
Depressed adults often show a bias towards negative self-referent processing at the expense of positive self-referent processing. The current study assessed whether a mental imagery intervention (Positive Self Reference Training—PSRT) delivered via the Internet could improve self-referent processing and depressive symptomatology among adults with moderate or greater depression symptoms. Participants were recruited via online methods and randomly assigned to one of two computerized interventions: active PSRT (n = 44) or control training (NTC; n = 43). The PSRT involved visualizing the self in response to different positive cues (e.g., an achievement) every other day for two weeks. The NTC provided neutral cues about objects. Self-referential processing of positive and negative adjectives and depression symptoms were measured at baseline, one week, and two weeks after initiating training. Over those two weeks, PSRT participants showed a greater increase in positive self-referent processing than did NTC participants. Negative self-referent processing and symptoms of depression declined comparably in both groups. Similarly, for both groups, increase in positive and decrease in negative self-referent processing was associated with a greater reduction in depression. These results indicate that mental imagery has the potential to improve self-referential processing, especially for positive stimuli, which may, in turn, help reduce depressive symptomatology.